Developing a virtual environment for viewing urban spatial planning and constructional features of an urban heritage site - the case of Fatehpur Sikri, India - Jahn Kassim, Puteri Shireen; Ibrahim, Mansor; Denan, Zuraini; Eusuf, Muhammad Abu; Mahmud, Murni; Abu Bakar, Juliana Aida (2008)
The paper discusses the processes of implementing virtual reality to highlight salient aspects of traditional urban planning and constructional aspects of a heritage complex; and the development of three dimensional (3D) user interfaces to view and navigate through the model.The interface allows flexible navigation to explore the space and construction of Fatehpur Sikri; however in some cases navigation is restricted by a guided sequence in order to enhance learning and understanding of the elements of architectural heritage.